‘The locals are friendly!’ An empirical analysis of mobility and mooring in travel blogs - Duffy, Andrew (2019)
While relations of power have been a repeated theme in studies on textual representations of guest–host interaction in travel and tourism, the emerging genre of travel blogs may offer a new perspective. This paper introduces the mobility/mooring paradigm as a framework for examining communications, looking initially at travel blogs. It proposes that bloggers both ‘moor’ their interactions with foreign locals in existing archetypes by representing them in stereotypical or generic terms; and represent them in ‘mobile’ terms, as individuals whose meaning is negotiable rather than fixed. Through qualitative and quantitative content analysis of travel blog posts, it finds that bloggers mostly report local people in positive terms, that these inhabitants written about mostly work in the tourism and service industries, and are mostly reported in ‘mobile’ terms that allows for re-negotiation of their identity through interaction. The implications for research into power in travel texts are discussed, as well as suggestions for future use of the mobilities/mooring paradigm in communication studies.